Effects of elevated CO2 concentration and experimental warming on morphological, physiological, and biochemical responses of winter wheat under soil water deficiency - Chang, Zhijie; Hao, Lihua; Lu, Yunze; Liu, Liang; Chen, Changhua; Shi, Wei; Li, Yue; Wang, Yanrui; Tian, Yinshuai (Frontiers in Plant Science, 2023)
Understanding the potential processes and mechanisms of crops in response to elevated CO2 concentration and temperature under soil water deficiency may further shed lights on the potential risks of climate change on the primary productivity and grain yield of agriculture. We examined the effects of elevated CO2 concentration (e[CO2]) and temperature (experimental warming) on plant biomass and leaf area, stomatal morphology and distribution, leaf gas exchange and mesophyll anatomy, rubisco activity and gene expression level of winter wheat grown at soil water deficiency with environmental growth chambers. We found that e[CO2] × water × warming sharply reduced plant biomass by 57% and leaf photosynthesis (Pn) 50%,